2017
DOI: 10.1248/cpb.c16-00744
|View full text |Cite
|
Sign up to set email alerts
|

Study of <i>O</i>-Allylation Using Triazine-Based Reagents

Abstract: Acid-catalyzed allylating reagent 2,4,6-tris(allyloxy)-1,3,5-triazine (TriAT-allyl) and its substituted derivatives have been developed. The reaction of acid-, and alkali-labile alcohols with these reagents in the presence of a catalytic amount of trifluoromethanesulfonic acid (TfOH) afforded the corresponding allyl ethers in good yields. Reactions using these reagents with an unsymmetrically-substituted regioisometric allyl group suggested that a single isometric allylic cation species would be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Allyl 6‐Bromohexyl Ether (7a‐allyl): Following GP‐2 with slight modification, 3 (13.7 mg, 40 µmol) was added to a mixture of 6a (54.5 µL, 0.400 mmol), ATTACK‐allyl (118.5 mg, 0.48 mmol), and molecular sieves 5 Å (50 mg) in 1,4‐dioxane (2.0 mL) at 50 °C. After 6.5 h, the reaction mixture was diluted with Et 2 O (10 mL) and filtered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allyl 6‐Bromohexyl Ether (7a‐allyl): Following GP‐2 with slight modification, 3 (13.7 mg, 40 µmol) was added to a mixture of 6a (54.5 µL, 0.400 mmol), ATTACK‐allyl (118.5 mg, 0.48 mmol), and molecular sieves 5 Å (50 mg) in 1,4‐dioxane (2.0 mL) at 50 °C. After 6.5 h, the reaction mixture was diluted with Et 2 O (10 mL) and filtered.…”
Section: Methodsmentioning
confidence: 99%
“…This reagent was then employed to convert alcohols and carboxylic acids into the corresponding benzyl ethers and esters, respectively, under non‐basic conditions. A series of triazine‐based acid‐catalyzed reagents were developed for p ‐methoxybenzylation, tert ‐butylation, and allylation . During the mechanistic studies on TriBOT, one of the intermediates, 6‐(benzyloxy)‐1,3,5‐triazine‐2,4(1 H ,3 H )‐dione (MonoBOT), was synthesized in two steps from 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Formation of 5-(triazinyloxy)oxazole is also reported to occur when an excess of DMT-MM was used. Recently, Jin and co-workers reported that Ni-catalyzed Suzuki–Miyaura coupling between triazinyloxybenzene and arylboronic acids affords the corresponding biaryl compounds [ 24 33 ]. In this context, we envisioned application of this Suzuki–Miyaura coupling to a 5-(triazinyloxy)oxazole would provide trisubstituted oxazoles ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Recently, we have developed several alkylating reagents based on the characteristics of 1,3,5-triazine. 2,4,6-Tris(benzyloxy)-1,3,5-triazine (TriBOT), 3,4) 2,4,6-tris(p-methoxybenzyloxy)-1,3,5-triazine (TriBOT-PM), 5) 6-(benzyloxy)-1,3,5-triazine-2,4(1H,3H)-dione (MonoBOT), 6,7) 2,4,6-tris(t-butoxy)-1,3,5-triazine (TriAT-tBu), 8) 2,4,6-tris(allyloxy)-1,3,5-triazine (TriAT-allyl), 9) and N,N′-dimethylated 6-(benzyloxy)-1,3,5-triazine-2,4(1H,3H)dione (DMBOT) 10) achieve the alkylation of various alcohols in good to excellent yields in the presence of a catalytic amount of an acid. 4-(4,6-Diphenoxy-1,3,5-triazin-2-yl)-4-benzylmorpholinium triflate (DPT-BM (X-a)) 11,12) converts acidor alkali-labile alcohols into corresponding benzyl ethers because of the nearly neutral conditions ( Fig.…”
mentioning
confidence: 99%